Research in the History of Economic Thought and Methodology : Including a Symposium on New Directions in Sraffa Scholarship. - Fiorito, Luca (Research in the history of economic thought and methodology., 2017)
Volume 35B of Research in the History of Economic Thought and Methodology features a symposium on the economics of Piero Sraffa, guest edited by Scott Carter and Riccardo Bellofiore. It also features general research contributions from Masazumi Wakatabe, and co-authors Eugene Callahan and Andreas Hoffman.